2013
DOI: 10.4103/0970-9371.112659
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic appendiceal goblet cell carcinoid masquerading as mucinous adenocarcinoma in effusion cytology: A diagnostic pitfall

Abstract: Goblet cell carcinoids are rare tumors of appendix having a mixed phenotype, with partial neuroendocrine differentiation and intestinal type goblet cell morphology. The reported incidence of this tumor is still limited. Till now, only two cases of metastatic goblet cell appendiceal carcinoid on effusion cytology have been reported in literature. We describe the clinico-pathological details and lay stress on fluid cytology of metastatic goblet cell carcinoid to ascitic fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Goblet cell carcinoid (GCC), an unique and enigmatic tumor involving the appendix almost exclusively, is a rare variant of appendiceal carcinoid [ 10 ]. Carcinoid tumors account for up to 85% of all appendiceal tumors, white, GCC accounts for only 6% of all appendiceal carcinoid tumors [ 11 ]. The term GCC was firstly introduced by Subbuswamy et al in 1974 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Goblet cell carcinoid (GCC), an unique and enigmatic tumor involving the appendix almost exclusively, is a rare variant of appendiceal carcinoid [ 10 ]. Carcinoid tumors account for up to 85% of all appendiceal tumors, white, GCC accounts for only 6% of all appendiceal carcinoid tumors [ 11 ]. The term GCC was firstly introduced by Subbuswamy et al in 1974 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports of metastatic GCC in effusion, and a few types of cells have been described. A common characteristic is signet‐ring cells with abundant cytoplasm and displaced nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…A common characteristic is signet‐ring cells with abundant cytoplasm and displaced nuclei. Gupta et al reported small cells in addition to signet‐ring cells; because of a background of mucin, they considered the tumor to be a metastatic mucinous carcinoma . Zafar et al described two types of cells other than signet‐ring‐like cells: small to intermediate size cells, and larger cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are rare cases of ostensibly primary extra-appendiceal GCC have been reported as stomach, duodenum, ampulla of Vater (21), jejunum, ileum, cecum, splenic flexure (22,23), ascending colon (24) and rectum (22,25,26,27,28).…”
Section: Mcdole Et Al From Washington University Inmentioning
confidence: 99%